Testing The Theory Of Planned Behavior And Perceived Risk To Predict Intention To Used Of Pay Later Services - Lubi, Ach.; Sanaji, Sanaji (Journal of Business and Management Review, 2023)
The phenomenon of increasing pay later consumers significantly from year to year has made many companies engaged in the technology industry vying to provide pay later services. However, from this there was a massive arrears made by consumers. Based on this phenomenon, the purpose of the authors in conducting this research is to determine the preference for the intention of using fintech and e-commerce consumers for pay later services by using TPB as a reference for this research and then adding one independent variable, namely perceived risk. This study use online survey and data will be analyzed using multiple regression analysis. The results of this study indicate that attitudes, subjective norms, perceived behavioral control, and perceived risk have a positive effect on the intention to use pay later services. Meanwhile, perceived risk has the smallest effect on the intention to use pay later services.